Review of the collection of documents «Sheikh Mansour in the materials of the Kizlyar and Mozdok commandant archives: a collection of documents / identification, archeographic. pro-cessing, preface, introductory article, comment., indexes by S.B. Manyshev. – M.: Publishing house "Kuchkovo field": X-HISTORY, 2022. – 464 p.» - Dmitry V. Ovsyannikov (Кавказология, 2024)
The study of the collection of papers and materials gathered by S.B. Manyshev "Sheikh Mansur in the materials of the Kizlyar and Mozdok commandant archives" published in Moscow in 2022 is provided. The reviewer describes both the document selection process and the conceptual pieces that come before the documentary component. A historiographical essay and examination of the history of Russian-Chechen relations in the framework of Mansur's Caucasus movement are critical for determining the current condition of modern historical research on this topic. The archaeographical prelude also informs the reader about the history of archive finances and the challenges of their maintenance. The reviewer praises the collection's high quality and the author-compiler's abilities.